2021
DOI: 10.3390/machines9110276
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamics of a Gyroscopic Rigid Rotor with Linear and Nonlinear Damping and Nonlinear Stiffness of the Elastic Support

Abstract: This study analytically and numerically modeled the dynamics of a gyroscopic rigid rotor with linear and nonlinear cubic damping and nonlinear cubic stiffness of an elastic support. It has been shown that (i) joint linear and nonlinear cubic damping significantly suppresses the vibration amplitude (including the maximum) in the resonant velocity region and beyond it, and (ii) joint linear and nonlinear cubic damping more effectively affects the boundaries of the bistability region by its narrowing than linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Damped beats observed in Figures 8 to 12, 14, and 15 occur due to the superposition of forced nonstationary oscillations and damped natural oscillations with frequencies that closely coincide with the vicinity of the resonance. 22…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Damped beats observed in Figures 8 to 12, 14, and 15 occur due to the superposition of forced nonstationary oscillations and damped natural oscillations with frequencies that closely coincide with the vicinity of the resonance. 22…”
Section: Resultsmentioning
confidence: 99%
“…Damped beats observed in Figures 8 to 12, 14, and 15 occur due to the superposition of forced nonstationary oscillations and damped natural oscillations with frequencies that closely coincide with the vicinity of the resonance. 22 According to equations (10), the direct modeling results can also be provided in the form of phase trajectories a 0 = a 0 a ð Þ and the dependence graph a = a b ð Þ of oscillating systems with different characteristics of nonlinear elasticity and different values of the coefficient of nonlinear cubic damping of the support, in Figures 16 and 17. Figure 16 shows that the value m 3 dampens not only angular misalignment a but also the angular velocity a 0 ; the sign change C 3 affects the size and density of phase trajectories.…”
Section: Nonstationary Resonant Transition and Their Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies in [1] , [2] , [3] confirmed that the restoring and damping properties of viscoelastic materials should be described in nonlinear models and it was found that rubber insulators have both nonlinear stiffness and nonlinear damping. Subsequently, nonlinear shock absorbers began to be studied both by analytical and numerical methods, as well as by experimental methods [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…In it, the vibration of the rotor with a flexible support containing springs or rubber sheets with rotor vibration with a rigid support base is compared in the experimental single-disk rotor system supported by ball bearings at both ends. The works [11] , [12] , [13] , [14] , [15] are devoted to the study of the combined effect of linear and nonlinear cubic damping on resonance and behind it stationary and non-stationary oscillations, and on the stability of the movement of a gyroscopic rigid rotor with linear rigidity and nonlinear cubic rigidity of an elastic support. In the case of a rigid nonlinear characteristic of an elastic support, it is proved that if linear viscous damping merely shifts the lower boundary of the instability region towards high rotation speeds, then nonlinear cubic damping narrows this region on all sides until it is completely eliminated [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%